1997
DOI: 10.1007/s004280050075
|View full text |Cite
|
Sign up to set email alerts
|

Intestinalization of gastric signet ring cell carcinomas with progression

Abstract: Recent developments in mucin histochemistry and immunohistochemistry have made reliable determination of the gastric and intestinal phenotypes of gastric carcinoma cells possible. Phenotypic expression changes from gastric epithelial cell type to intestinal epithelial cell type with the growth of gastric tumours in experimental animals. We studied cell differentiation in gastric signet ring cell carcinomas with progression in 203 surgically obtained specimens. The results showed that the proportion of gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 23 publications
4
65
1
Order By: Relevance
“…[29][30][31][32][33] By sequential observation of rat glandular stomach carcinomas and comparisons of phenotypic expression of human gastric carcinoma cells between early and advanced cases, a phenotypic shift from gastric to intestinal epithelial cell type expression has been recognized with progression of each histological type of gastric carcinomas. [33][34][35][36] The present results regarding phenotypic expression of tumor cells showed that mouse glandular stomach adenomas and carcinomas consist solely of tumor cells of gastric epithelial cell type, without any intestinal metaplasia in the mucosa surrounding carcinomas. Thus, differentiated and undifferentiated type carcinomas arise from gastric proper mucosa independently of intestinal metaplasia in this model.…”
Section: Discussionmentioning
confidence: 96%
“…[29][30][31][32][33] By sequential observation of rat glandular stomach carcinomas and comparisons of phenotypic expression of human gastric carcinoma cells between early and advanced cases, a phenotypic shift from gastric to intestinal epithelial cell type expression has been recognized with progression of each histological type of gastric carcinomas. [33][34][35][36] The present results regarding phenotypic expression of tumor cells showed that mouse glandular stomach adenomas and carcinomas consist solely of tumor cells of gastric epithelial cell type, without any intestinal metaplasia in the mucosa surrounding carcinomas. Thus, differentiated and undifferentiated type carcinomas arise from gastric proper mucosa independently of intestinal metaplasia in this model.…”
Section: Discussionmentioning
confidence: 96%
“…These findings may suggest that the increased proportion of I type during submucosal invasion is caused not by the acquisition of intestinal marker expression, but by a reduction of gastric marker expression. In contrast, previous reports have shown that the phenotype of signet-ring cell carcinomas alters from gastric phenotype to intestinal phenotype during submucosal invasion [11][12][13]. It may be argued that reduced gastric phenotypic expression in the submucosal part could be caused by the selective submucosal invasion of constitutively non-gastrictype cells.…”
Section: Discussionmentioning
confidence: 74%
“…Previous investigations of the phenotypic expression of undifferentiated-type adenocarcinomas are limited, and it has been reported that there are some undifferentiated-type adenocarcinomas of intestinal phenotype [9,10], and that the intestinal phenotype in gastric signet-ring cell carcinomas appears to occur during tumor progression [11][12][13] or during tumor spread in the mucosa [14]. However, how frequent and when phenotypic alteration occurs during the development of undifferentiated-type adenocarcinomas remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 18 of 19 cases with the CSP were undifferentiated adenocarcinoma, and 17 of these had a gastric component, and no I-type was found in this study. Since I-type early undifferentiated adenocarcinoma is very rare (Yamachika et al, 1997), its vascular construction is unclear. Further accumulation of cases of I-type early undifferentiated adenocarcinoma in the future may clarify whether the CSP is characteristic of G-type undifferentiated adenocarcinoma or of all types including I-types of undifferentiated adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells were functionally (mucus productivity) well differentiated, although the glandular duct structure was undifferentiated. Early undifferentiated gastric cancer is comprised of the G-type and I-type cancer cells, which increase with progression (Yamachika et al, 1997) while organoid differentiation may be lost. Therefore, the CSP is characteristic of the early stage of G-type undifferentiated adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%